Correlation of Malondialdehyde (MDA) and C-reactive Protein (CRP) Level to Neurodevelopmental Outcome in Children After the Episode of Convulsive Type Status Epilepticus - Restuningwiyani, Sintha; Ariani, Ariani; Sujuti, Hidayat; Rahayu, Masruroh; Subandiyah, Krisni (Journal of Tropical Life Science, 2018)
Refractory and mortality associated with status epilepticus (SE) were correlated with the degree of inflammation-induced neuronal cell death. This study was aimed to investigate the correlation of oxidative stress (Malondialdehyde, MDA) and inflammation (C-reactive protein, CRP) process with neurodevelopmental outcome in children after the episode of convulsive type SE. This study was designed as cross sectional which included 26 convulsive type SE subjects and 15 control subjects. MDA level was measured by thiobarbituric acid (TBA) method, while CRP level was measured by ELISA method. Neurodevelopmental outcome was measured by Bayley-III Scale of Infant and Toddler Development 3 month after the convulsive type SE episode. Results showed that both MDA (independent t-test, p < 0.05) and CRP (Mann-Whitney test, p < 0.05) level was significantly higher in convulsive type SE group as compared to control group. Further analysis also showed that MDA (Spearman correlation test, p = 0.000, r = 0.756) and CRP (Spearman correlation test, p = 0.000, r = 0.835) level was positively correlated with convulsive type SE. In convulsive type SE group, MDA level was negatively correlated with neurodevelopmental outcome but CRP was not. We concluded that MDA level was negatively correlated with neurodevelopmental outcome in children with convulsive type SE, but CRP was not.